1999
DOI: 10.1002/(sici)1097-4598(199909)22:9<1201::aid-mus6>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve dysfunction in hereditary motor and sensory neuropathy type I and III

Abstract: Facial nerve function was studied in 19 patients with hereditary motor and sensory neuropathy type I (HMSN I) and 2 patients with hereditary motor and sensory neuropathy type III (HMSN III, Dé jé rineSottas), and compared to that in 24 patients with Guillain-Barré syndrome (GBS). The facial nerve was stimulated electrically at the stylomastoid fossa, and magnetically in its proximal intracanalicular segment. Additionally, the face-associated motor cortex was stimulated magnetically. The facial nerve motor neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…12 Consistent with this observation was that the facial motor study commonly had prolonged latency in inherited demyelinating cases. 13 Normative data for blink reflex studies have been generated by different groups, with 13 ms being the upper limit of normal for the R1 response for individuals > age 2 years 14 and R2 being less useful due to much greater variability. 12,15 Here, we evaluated the use of blink reflex R1 latency to distinguish demyelinating from axonal inherited polyneuropathies through a study of blink reflex responses in genetically confirmed patients.…”
mentioning
confidence: 99%
“…12 Consistent with this observation was that the facial motor study commonly had prolonged latency in inherited demyelinating cases. 13 Normative data for blink reflex studies have been generated by different groups, with 13 ms being the upper limit of normal for the R1 response for individuals > age 2 years 14 and R2 being less useful due to much greater variability. 12,15 Here, we evaluated the use of blink reflex R1 latency to distinguish demyelinating from axonal inherited polyneuropathies through a study of blink reflex responses in genetically confirmed patients.…”
mentioning
confidence: 99%